Integral Sliding Mode Control: A Review of Applications - Gopikadev Y.; Amal A. (International Journal of Advanced Control and System Engineering, 2024)
Integral Sliding Mode Control (ISMC) has emerged as a robust and efficient method for handling nonlinear systems with uncertainty, turbulence and external disturbances. This study provides a detailed review of ISMC and its design foundations, design methods, practical application aspects and recent developments are included. ISMC design methodology is explored, to be extended with various design methods with different design methods. Recent advances in research, chatter reduction techniques, applications in specific areas, theoretical design advances, or comparative analysis with other control methods in addressing the challenges associated with ISMC are discussed in this study. Practical aspects of ISMC applications are discussed, including actuator saturation mitigation, robustness to model uncertainties, and sensor fusion techniques. Furthermore, various applications and case studies in various industries are presented to demonstrate ISMC efficiency and performance of complex problem solving. The effectiveness of these improvements are scrutinized, such as crime and the complexity of their controls. In addition, the study discusses the potential of ISMC in various applications and identifies promising future research directions in this policy topic. Finally, recent developments and possible future research directions in ISMC are outlined, highlighting topics such as ISMC with specialized systems, distributed ISMC, artificial intelligence, and emerging technologies such as the Internet; an integration will be emphasized.
Keywords: Integral sliding mode control; Sliding mode control; radial basis functional neural networks